1995
DOI: 10.1007/bf02368356
|View full text |Cite
|
Sign up to set email alerts
|

Trophic interactions between zooplankton andPhaeocystis cf.globosa

Abstract: Mesozooplankton grazing on Phaeocystis cf. globosa was investigated by laboratory and field studies. Tests on 18 different species by means of laboratory incubation experiments, carried out at the Biologische Anstalt Helgotand, revealed that Phaeocystis was ingested by 5 meroplanktonic and 6 holoplanktonic species; filtering and ingestion rates of the latter were determined. Among copepods, the highest feeding rates were found for Calanus helgolandicus and Temora longicornis. ton grazing by the dominant copepo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 31 publications
(18 reference statements)
1
24
0
Order By: Relevance
“…in the conversion from dimethylsulfoniopropionate (DMSP) to dimethylsulfide (DMS), is considered an antibiotic (Sieburth, 1960) and other growth and grazing inhibitors could be released by this species as well (Nejstgaard et al, 2007, but see Turner, 2015). The production of toxins by phytoplankton has lethal or sub-lethal effects on the microzooplankton, both for ciliates or tintinnids (Verity and Stoecker, 1982;Carlsson et al, 1990;Hansen, 1995). Rosetta and McManus (2003) concluded that ciliates may exert grazing pressure on HAB species early on, potentially contributing to the suppression and decline of Prymnesium minimum and P. parvum before they bloomed, but that ciliate grazing would be relatively ineffective once blooms (and toxicity) developed fully.…”
Section: Microzooplankton Grazingmentioning
confidence: 99%
“…in the conversion from dimethylsulfoniopropionate (DMSP) to dimethylsulfide (DMS), is considered an antibiotic (Sieburth, 1960) and other growth and grazing inhibitors could be released by this species as well (Nejstgaard et al, 2007, but see Turner, 2015). The production of toxins by phytoplankton has lethal or sub-lethal effects on the microzooplankton, both for ciliates or tintinnids (Verity and Stoecker, 1982;Carlsson et al, 1990;Hansen, 1995). Rosetta and McManus (2003) concluded that ciliates may exert grazing pressure on HAB species early on, potentially contributing to the suppression and decline of Prymnesium minimum and P. parvum before they bloomed, but that ciliate grazing would be relatively ineffective once blooms (and toxicity) developed fully.…”
Section: Microzooplankton Grazingmentioning
confidence: 99%
“…From the analysis of the previous section, we see that as θ crosses a certain value, namely, θ 0 , two roots of the eigenvalue equation (16) will cross the imaginary axis as a pair of complex conjugates. The solutions to the linearised system will be proportional to e iq·x · e iωt , which implies that the bifurcating solution is periodic both in space and time.…”
Section: Construction Of Bifurcating Solutionsmentioning
confidence: 95%
“…Substituting (34) in (16), separating real and imaginary parts and differentiating partially we find…”
Section: Theorem 42mentioning
confidence: 99%
See 1 more Smart Citation
“…Because species of zooplankton such as copepods, have feeding preferences for different species of phytoplankton (Davies et al, 1992), and because they in turn are important links in the marine food web, the change in Phaeocystis abundance could weU have important implications for coastal North Sea ecosystems in general and for fisheries in particular. Yet even a partial untangling of the effects on the food web is a slow process requiring dedicated, painstaking work (Hansen, 1994).…”
Section: Ecology -The Achilles Heel Of Monitoringmentioning
confidence: 99%